The relationship between self-perceived burden, depression, medication adherence, and health-related quality of life in coronary heart disease patients - Lim, Benjamin Chee Chong (2017)
The feeling of being a burden to others, also known as self-perceived burden, is an understudied construct among patients with chronic illnesses, despite its numerous potentially detrimental consequences on the patient’s health and well-being. Although self-perceived burden has been consistently linked to health-related quality of life (HRQOL), its underlying mechanisms remain unexplored, particularly in coronary heart disease (CHD) patients. Furthermore, to date, no studies investigated the relationship between self-perceived burden and medication adherence in heart patients. The present cross-sectional study aims to address these research gaps by empirically examining the relationships between self-perceived burden and its correlates in heart patients. One hundred twenty-two CHD patients were recruited from a cardiac rehabilitation centre. Participants completed questionnaires pertaining to self-perceived burden, depression, medication adherence, and HRQOL. Hierarchical regression analyses were performed. The results revealed that depression (1) mediated the effect of self-perceived burden on physical HRQOL, and (2) partially mediated the effect of self-perceived burden on social HRQOL. However, self-perceived burden did not predict medication adherence. Additionally, medication adherence did not mediate the effect of (1) self-perceived burden on physical HRQOL, and (2) self-perceived burden on social HRQOL. These findings suggested that self-perceived burden and depression may be two vital cardiovascular risk factors health-care practitioners could consider during early patient screenings to enhance existing cardiac programmes, which in turn improve cardiac patients’ prognosis and overall quality of life (QOL).